Chains of tragedy: The impact of bullying victimization on mental health through mediating role of aggressive behavior and perceived social support - Guo, Yi; Tan, Xiao; Zhu, Qiu-jin (Frontiers in Psychology, 2022)
Objective Bullying is a worldwide concern for its devastating consequences. The current study focused on bullying victims, examining the effects of being bullied on mental health and the chain of mediating mechanisms among adolescents. Specifically, this study attempts to explain the relationship between bullying victimization and mental health from the perspective of maladaptive behavior and perceived social support. Methods A total of 3,635 adolescents responded to questions on bullying victimization, aggressive behavior, perceived social support, and mental health measurements including anxiety, depression, and subjective well being scale combined. Results (1) Bullying victimization was significantly correlated with aggressive behavior, perceived social support, and mental health, including anxiety, depression, and subjective well being. (2) Bullying victimization not only negatively predicts mental health levels but also has an indirect impact on mental health through three pathways: a separate mediating effect on aggressive behavior, a separate mediating effect on perceived social support, and a chain mediating effect on both. Conclusion The present results demonstrate that maladaptive behavior by bullying victims can lead to changes in their perceived social support and mental health problems. Violence begets violence and provides no constructive solutions, instead, produces a tragic chain of victimization. Further implications are discussed accordingly.